Medial Patellofemoral Ligament Reconstruction in Obese Patients Results in Low Complication Rates and Improved Subjective Outcomes - Seth L. Sherman, M.D; Joseph M. Rund, M.D; John W. Welsh, M.D; Taylor Ray; John R. Worley, M.D; Lasun O. Oladeji, M.D; Aaron D. Gray, M.D; Betina B. Hinckel, M.D., Ph.D (Elsevier, 2023)
Purpose: To compare outcomes, activity scores, and complication rates of obese and non-obese patients undergoing medial patellofemoral ligament (MPFL) reconstruction. Methods: A retrospective review identified patients undergoing MPFL reconstruction for recurrent patellofemoral instability. Patients were included if they had undergone MPFL reconstruction and had follow-up for a minimum of 6 months. Patients were excluded if they underwent surgery less than 6 months earlier, had no outcome data recorded, or underwent concomitant bony procedures. Patients were divided into 2 groups based on body mass index (BMI): BMI of 30 or greater and BMI less than 30. Presurgical and postsurgical patient-reported outcomes including Knee Injury and Osteoarthritis Outcome Score (KOOS) domains and the Tegner score were collected. Complications requiring reoperation were recorded. P < .05 was defined as a statistically significant difference. Results: A total of 55 patients (57 knees) were included. There were 26 knees with a BMI of 30 or greater and 31 knees with a BMI less than 30. There were no differences in patient demographic characteristics between the 2 groups. Preoperatively, no significant differences were found in KOOS subscores or Tegner scores (P = .21) between groups. At minimum 6-month follow-up (range, 6.1-70.5 months), patients with a BMI of 30 or greater showed statistically significant improvements in the KOOS Pain, Activities of Daily Living, Symptoms, and Sport/Recreation subscores. Patients with a BMI less than 30 showed a statistically significant improvement in the KOOS Quality of Life subscore. The group with a BMI of 30 or greater had significantly lower KOOS Quality of Life (33.34 ± 19.10 vs 54.47 ± 28.00, P = .03) and Tegner (2.56 ± 1.59 vs 4.78 ± 2.68, P = .05) scores. Complication rates were low, with 2 knees (7.69%) requiring reoperation in the cohort with a BMI of 30 or greater and 4 knees (12.90%) requiring reoperation in the cohort with a BMI less than 30, including 1 reoperation for recurrent patellofemoral instability (P = .68). Conclusions: In this study, MPFL reconstruction in obese patients was safe and effective, with low complication rates and improvements in most patient-reported outcomes. Compared with patients with a BMI less than 30, obese patients had lower quality-of-life and activity scores at final follow-up. Level of Evidence: Level III, retrospective cohort study.